2018
DOI: 10.1007/s00467-018-3983-6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging studies in pediatric fibromuscular dysplasia (FMD): a single-center experience

Abstract: Limitations of the study include the sample size and biases-only patients diagnosed with FMD were included in this study and most patients were referred to a pediatric nephrologist for unexplained hypertension. Angiography should be performed as part of the initial work-up of any child suspected of having renovascular FMD, regardless of the findings seen on US, MRA, or CTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 28 publications
(63 reference statements)
5
22
0
1
Order By: Relevance
“…In contrast, in a recent study conducted on only RVH or pediatric patients with FMD, Trautmann et al reported a sensitivity of 93% and a specificity of 50% utilizing CTA in 34 pediatric patients with RVH, 6 while Louis et al reported a sensitivity of 84.2% (16/19) and a specificity of 70% (7/10). 20 In our analysis, the 3D images obtained via CTA were almost identical to those obtained via DSA and CTA seemed to be sufficient to detect stenosis or obstruction of the renal artery, identify the ischemic region of the kidney, and diagnose RVH. Still, we have to note that the real-time display of DSA was useful for the evaluation of the collateral vessel and showed the blood supply for the affected ischemic kidney pole.…”
Section: Discussionsupporting
confidence: 53%
“…In contrast, in a recent study conducted on only RVH or pediatric patients with FMD, Trautmann et al reported a sensitivity of 93% and a specificity of 50% utilizing CTA in 34 pediatric patients with RVH, 6 while Louis et al reported a sensitivity of 84.2% (16/19) and a specificity of 70% (7/10). 20 In our analysis, the 3D images obtained via CTA were almost identical to those obtained via DSA and CTA seemed to be sufficient to detect stenosis or obstruction of the renal artery, identify the ischemic region of the kidney, and diagnose RVH. Still, we have to note that the real-time display of DSA was useful for the evaluation of the collateral vessel and showed the blood supply for the affected ischemic kidney pole.…”
Section: Discussionsupporting
confidence: 53%
“…Meyers et al in their single center study of 25 children with FMD showed CTA to be the most sensitive among the three modalities, but the study also produced 30% false positive results. The DSA was the only procedure that was 100% sensitive and specific, had 100% PPV and NPV, and the showed the distal vessel disease [11]. Recently, the European Society of Hypertension and Society for Vascular Medicine's first international Consensus on FMD also recommended the CTA of the RAs as the first non-invasive imaging modality of choice [5], with an RA duplex reserved only for centers with extensive experience with the duplex.…”
Section: Discussionmentioning
confidence: 99%
“…Though any vasculature can be affected, the RAs are involved in 97% of children with FMD; mesenteric and abdominal aorta are other commonly affected sites, with carotids less affected in children than in adults [9,10]. A renal bruit is heard in only a very small subset of children with FMD [11]. The management of renal artery FMD includes medical therapy and surveillance, endovascular therapy (angioplasty with or without stenting), or surgery.…”
mentioning
confidence: 99%
“…There is limited experience of COVID-19 infection in tuberculosis (TB) patients, but it is estimated that there may be a catastrophic impact of COVID-19 on TB [1]. This pandemic of COVID-19 has elicited social stigmata and discriminatory behaviour, coupled with preexisted TB related stigmata [2,3]. Together, it is likely to increase the burden on the family as well as on limited resources in developing countries.…”
Section: Tuberculosis During Covid-19 Pandemic: Challenges and Opportmentioning
confidence: 99%
“…We read the recently published articles on vitamin D deficiency in the journal [1,2], and wish to raise certain related issues. We believe that the true burden of vitamin D deficiency/ insufficiency and its associations cannot be estimated unless a standard consensus definition is used.…”
Section: Pediatric Renovascular Hypertension: the Diagnostic Algorithmmentioning
confidence: 99%